Reintroduction failure after negative peanut challenges in children. Issue 6 (October 2014) - van Erp, Francine C.; Boot, Jenneke; Knulst, André C.; Pasmans, Suzanne G. M.; van der Ent, Cornelis K.; Meijer, Yolanda
Abstract Background A negative double‐blind placebo‐controlled food challenge (DBPCFC) should normally be followed by reintroduction of the food. However, reintroduction fails in a subset of children. The observed reintroduction problems could be due to refusal of the food that long has been avoided, to other behavioural/psychological factors or to false negative DBPCFC outcome. This study analyses the frequency, causes and risk factors for reintroduction failure in children after negative peanut DBPCFC. Methods A retrospective study of children with a negative DBPCFC for peanut was performed. During follow‐up after DBPCFC, parents were systematically interviewed about the current diet, symptoms and problems during reintroduction, and reactions to peanut after the reintroduction period. Successful reintroduction was defined as eating peanut or products containing peanut as ingredient on a regular basis. Results Follow‐up data were obtained in 103 children with a negative peanut challenge. In 70 (68%) children, reintroduction was successful (54 children tolerated peanut, 16 children tolerated peanut as ingredient). Reintroduction failed in 33 (32%) children. Food refusal (45%) and peanut‐related symptoms (33%) were the most reported reasons. Risk factors for reintroduction failure were an elimination diet for more than three other foods (p = 0.019), a long elimination diet for peanut (p = 0.048) and peanut‐related symptoms at home (p = 0.002). Conclusion Reintroduction failure is a common problem in children after negative peanut challenge. To guide reintroduction and identify potential peanut‐related symptoms at home, careful follow‐up after negative DBPCFC is advised. When symptoms occur or persist, food challenge outcome needs to be reconsidered.